Low occurrence of HBsAg but high frequency of transient occult HBV infection in vaccinated and HBIG‐administered infants born to HBsAg positive mothers. Issue 12 (29th August 2017) - Zhou, Shan; Li, Tingting; Allain, Jean‐Pierre; Zhou, Bin; Zhang, Yuming; Zhong, Mei; Fu, Yongshui; Li, Chengyao
Abstract : The status of chronic and occult HBV infection (OBI) in neonatal hepatitis B vaccine and immunoglobulin (HBIG) vaccinated infants born to HBsAg+ mothers was investigated at a major hospital in China. Seventy‐seven and 15 blood samples were collected in first or second follow‐up detection from the vaccinated babies aged 3‐36 months born to 43 HBsAg+ or plus 25 HBeAg+ mothers. HBV infection was analyzed between the paired baby and mother by serology and DNA analysis. Among 77 children born to 68 HBsAg+ mothers, 3.9% (3/77) were HBsAg+, and 36.4% (28/77) were HBV DNA+/HBsAg− (OBIs) by a single PCR, respectively. Thirteen of 28 HBV DNA+/HBsAg− samples were conformed by two PCRs or S sequence, which accounted for 16.9% (13/77) of children. Three HBsAg+ and six OBIs were genotyped in consistent with their mother's HBV strains. Of 77 babies' blood samples, anti‐HBs reactivity varied slightly according to age groups, while passively transmitted anti‐HBc reactivity declined from 100% high reactivity at age 3‐5 months to mostly negative at age ≥12 months. Babies with apparent OBI had higher levels of anti‐HBc and lower levels of anti‐HBs than those without OBI but all eight OBI babies with second follow‐up samples became HBV DNA negative beyond 1 year of age. The vaccinated infants born to HBsAg+ mothers presented the low rate of HBsAg occurrence as vaccination failure and high frequency of viral persistence in the form of transient OBIs since no evidence of active HBV infection occurred beyond 1 year of age.